Zambia Economic Brief, June 2016, Issue 7 : Beating the Slowdown--Making Every Kwacha Count - World Bank Group (World Bank, Lusaka, 2016)
The external environment confronting Sub-Saharan Africa (SSA) is expected to remain difficult in the near term. Commodity prices are expected to remain low, and in 2016, growth in the region isforecast to drop to 2.5 percent from 3.0 percent in 2015 (World Bank forecast). There is considerable variation in economic performance across countries, with the slowdown concentrated among the region's largest commodity exporters. Growing economic vulnerabilities, amid weakened policy buffers, continue to pose challenges for policy makers. The balance of risks to the outlook remains tilted to the downside. The global risks include: (i) a sharper than expected slowdown in China (as the country rebalances growth toward consumption and services), (ii) a further decline in commodity prices, and (iii) tighter global financing conditions that would result in higher borrowing costs and reduced sovereign bond access for emerging and frontier countries. On the domestic front, delays in adjustment to external shocks in affected countries would create policy uncertainties that could weigh on investor sentiment and weaken the recovery.